Energy crises in perspective - Fisher, John Crocker (New York : Wiley, 1974)
This book is written for people with a general or professional interest in world energy activities who might like to see an undistorted picture of the world energy situation as it is, how it got there, and where it is going. The book contains discussion about: 1) the role of energy. 2) the sources of energy. 3) projected energy consumption. 4) energy resources. 5) economies of scale and new technology. 6) social and environmental factors. 7) political factors. 8) availability of fuels. 9) role of electricity. 10) efficiency of energy utilization. 11) progress of electrification. 12) electric generation technologies. 13) factors affecting the cost of electricity; and 14) comparison of fossil fuel, nuclear, and solar electricity.
"A Wiley-Interscience publication."
Includes bibliographical references and index.
ne 19/04/2018
Loans
Keywords: Power Resources; Energy policy